1997
DOI: 10.1093/ajcn/65.4.977
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized study of glutamine-enriched parenteral compared with enteral feeding in postoperative patients

Abstract: Plasma amino acids were measured in 17 postoperative subjects randomly assigned to receive for > or = 5 d tube feeding or total parenteral nutrition (TPN) that had identical energy, nitrogen, and glutamine contents. Subjects required gastric or pancreatic surgery for malignancy and were well-matched for age and body mass index. Tube feeding or TPN began on postoperative day 1 and advanced in daily 25% increments to meet goals of 105 kJ . kg body wt-1 . d-1, 1.5 g protein . kg body wt-1 . d-1, and 0.3 g glutami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Recent studies have shown that early enteral nutrition (EEN) provides better clinical course than TPN. Furthermore, some special nutritional substance like glutamine has potential benefits (Fish et al, 1997;Abou-Assi and O'Keefe, 2002) In many studies investigating the effects of glutamine, it was reported that complications were reduced by nutritional support (Ziegler et al, 1996(Ziegler et al, , 1997Morlion et al, 1998;Ockenga et al, 2002). In this study, complications developed in 10% of the patients in treatment group, whereas in 40% of the patients in control group.…”
Section: Discussionmentioning
confidence: 57%
“…Recent studies have shown that early enteral nutrition (EEN) provides better clinical course than TPN. Furthermore, some special nutritional substance like glutamine has potential benefits (Fish et al, 1997;Abou-Assi and O'Keefe, 2002) In many studies investigating the effects of glutamine, it was reported that complications were reduced by nutritional support (Ziegler et al, 1996(Ziegler et al, , 1997Morlion et al, 1998;Ockenga et al, 2002). In this study, complications developed in 10% of the patients in treatment group, whereas in 40% of the patients in control group.…”
Section: Discussionmentioning
confidence: 57%
“…Little data are available comparing the metabolic effects of Gln when given by enteral versus parenteral routes (14,26). Also, metabolic results with enteral Gln administration have been inconsistent across studies (27,28).…”
Section: Discussionmentioning
confidence: 99%
“…There is some evidence that the body glutamine pool is slower to recover when the same dose of glutamine is given enterally (orally) as opposed to parenterally (Fish et al 1997). The enteral route may be ideal when given early to the noninfected patient to improve gut-associated lymphoid tissue function and immune defense against infection, but for already severely stressed or infected ICU patients, enteral supplements alone may be inadequate, and parallel parenteral support is likely to be required.…”
Section: Implications For Glutamine Dipeptide Therapymentioning
confidence: 99%